INFLUENCE OF ELECTRONIC WORD-OF-MOUTH ON CONSUMER BEHAVIOUR - DAOUDI MOUAD (CHAKOR Abdellatif, 2021)
Electronic word-of-mouth (e-WOM) is the exchange of experiences and information between consumers to help each other make purchasing decisions. Therefore, if consumers are satisfied with their experience, they are likely to pass on positive e-Wom. Similarly, businesses place great importance on consumer feedback, as negative consumer feedback can generate a negative WOM. Studies have shown that social media attributes, such as social presence and interactivity, affect the level of consumer e-business behaviour. There are credible reasons to believe that trust is a major challenge for organisations wishing to use e-commerce to achieve their objectives. This paper focuses on a review of the literature on the influence of electronic word-of-mouth on consumer behaviour. We present our analysis in different aspects. First, we develop models of purchase behaviour including the theory of planned behaviour and models of consumer decision making, and second, the information processing of e-word including the characteristics and motivations of the recipient of the e-word message, the information processing models, and the evaluation and filtering process of e-word messages. Finally, we discuss the behaviour that follows the reading of electronic word-of-mouth messages.